IMPLEMENTATION OF HEALTH SERVICES IN CLASS II B TAKENGON PRISON - Mudfar Alianur; Nurlaila Nurlaila; Alena Alena (Universitas Islam Negeri Ar-Raniry, 2022)
Law No. 12 of 1995 article 14 (1) concerning correction which in Letter (d) states that prisioners receive healt services and proper food. Inadequate health services are one of the impacts that can be felt by the inmates of the class II B Takengon Prison, which affect prisoners’ health. In this study, the author discussed the way on how prosiners’ health has been implemented in class II B Takengon prison. This study used an empirical legal research method which tried to explain fact in the field through interviews or direct observation. This study aimed to find out how the implementations of health services for inmates in Class II B Takengon Prison. The result showed that the implementation of health services for the inmates in the Class II B Takengon Prison is not optimal due to the lack of healthcare workers such as dentists and slow process of fund disbursement which affects the limitation of medicine availability as well as inadequate health facilities. It can be concluded that the implementation of health services for inmates in the Class II B Takengon is not optimal and the facilities is inadequate. The researcher suggests that Takengon prison should improve health services and add more health facilities.